Pengaruh Kualitas Pelayanan dan Promosi terhadap Kepuasan Wisatawan pada Destinasi Wisata di Kota Sabang - Vilzati Vilzati; T. Andi Roza; A. Hamid; Zuliani Zuliani; Ikhsan Fajri (Jurnal Ragam Pengabdian, 2026)
This study aims to examine the effect of service quality and promotion on tourist satisfaction at tourism destinations in Sabang City. Tourist satisfaction is one of the key indicators of successful destination management, influenced by the ability of destination managers to provide high-quality services and implement effective promotional strategies. This study employed a quantitative approach using a survey method. The research sample consisted of 100 tourists selected through an accidental sampling technique. Data were collected using a five-point Likert scale questionnaire and analyzed using IBM SPSS Statistics 25 through descriptive statistical analysis and multiple linear regression.The descriptive analysis showed that the mean score for service quality was 20.20 out of a maximum score of 25, promotion scored 12.63 out of 15, and tourist satisfaction scored 12.27 out of 15. These findings indicate that tourists perceived both the service quality and promotional activities of tourism destinations in Sabang City positively. The results further revealed that service quality and promotion have a positive and significant effect on tourist satisfaction, indicating that improvements in service quality and the effectiveness of promotional activities are associated with higher levels of tourist satisfaction. This study implies that tourism destination managers and local governments should continuously improve service quality, strengthen human resource competencies, and optimize promotional strategies, particularly through digital media, to enhance tourist satisfaction, encourage repeat visits, and strengthen the competitiveness of Sabang City's tourism sector.